(untitled) (University of Warwick Press, 2019)
This self-study guide for students of German was designed with special attention to students’ needs, providing an accessible and practical way to revise grammar topics that prove to be common mistakes or stumbling blocks when learning German as a speaker of English. This guide is aimed at German learners at all levels, but especially at those with a good basic command of the language seeking to dispose of typical mistakes and to consolidate their knowledge of key grammatical structures. The idea is to spend no more than a few minutes a day on one topic. Although this is primarily a grammar guide, it also provides opportunities to learn about German (as well as Austrian and Swiss) culture and life by embedding grammar in a wider context.